2021
DOI: 10.3892/mmr.2021.12425
|View full text |Cite
|
Sign up to set email alerts
|

Emodin inhibits the progression of acute pancreatitis via regulation of lncRNA TUG1 and exosomal lncRNA TUG1

Abstract: Acute pancreatitis (AP) is one of the most frequent gastrointestinal diseases and has no specific treatment. It has been shown that dysfunction of pancreatic acinar cells can lead to AP progression. Emodin is a natural product, which can alleviate the symptoms of AP. However, the mechanism by which emodin regulates the function of pancreatic acinar cells remains unclear. Thus, the present study aimed to investigate the mechanism by which emodin modulates the function of pancreatic acinar cells. To mimic AP in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Lnc-MKRN2-42 : 1 in exosomes from plasma samples is positively correlated with MDS-UPDRS III scores in patients with Parkinson's disease, and it may be involved in the development of Parkinson's disease [ 8 ]. Only one paper has reported the involvement of exosomal lncRNA in the progression of acute pancreatitis, that is, rhodopsin suppresses acute pancreatitis by regulating the expression of cellular and exosomal lncRNA TUG1 [ 9 ]. The effect of lncRNA in NAFLD-derived exosomes on pancreatitis has not been explored previously.…”
Section: Introductionmentioning
confidence: 99%
“…Lnc-MKRN2-42 : 1 in exosomes from plasma samples is positively correlated with MDS-UPDRS III scores in patients with Parkinson's disease, and it may be involved in the development of Parkinson's disease [ 8 ]. Only one paper has reported the involvement of exosomal lncRNA in the progression of acute pancreatitis, that is, rhodopsin suppresses acute pancreatitis by regulating the expression of cellular and exosomal lncRNA TUG1 [ 9 ]. The effect of lncRNA in NAFLD-derived exosomes on pancreatitis has not been explored previously.…”
Section: Introductionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is one of the most frequent gastrointestinal diseases and has no specific treatment. It has been shown that dysfunction of pancreatic acinar cells can lead to AP progression [2]. In AP, gut barrier injury resulting in increased mucosal permeability may lead to translocation of intestinal bacteria, necrosis of pancreatic and peripancreatic tissue, and infection, often accompanied by multiple organ dysfunction syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to ALI, TUG1 and exosomal TUG1 expression was stimulated to be upregulated in AR42J cells and was significantly associated with Treg cell differentiation. The overexpression of TUG1 promotes LPS/cerulein-induced apoptosis and inflammation in AR42J cells [ 52 ]. According to recent research, lncRNA TUG1 may play opposing roles in AP and ALI.…”
Section: Exosome-specific Ncrnasmentioning
confidence: 99%
“…Several in vivo and in vitro studies demonstrated emodin’s protective properties against AP-induced pancreatic injury, intestinal barrier dysfunction, and ALI [ 23 , 167 ]. Emodin was discovered to boost the differentiation and anti-inflammatory activity of regulatory T cells by stimulating the release of exosome-specific lncRNA taurine upregulated 1 (TUG1) from pancreatic acinar cells, hence limiting the development of AP [ 52 ]. Recent research suggests that the inflamed pancreas may release exosomes into the circulation during SAP.…”
Section: The Therapeutic Potential Of Exosomes In Ap and Associated Alimentioning
confidence: 99%